Educating Through Social Media: A Communication Strategy in Instilling Unity Value - Puri Bestari Mardani; Maria Febiana Christanti (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2022)
Kalijodo's transformation into a Green Open Space and Child-Friendly Integrated Public Space drew many people from outside the community, including immigrants who settled and became new residents. Conflicts arise as a result of cultural differences between old and new residents. The community organization that manages the Kalijodo area tries to educate residents about the value of unity by creating a unifying song distributed via social media, YouTube; this is interesting for further research. This study focuses on the communication strategy used by the community organization in charge of Kalijodo to bring its citizens together. This study employs Paul A Argenti's (2013) communication strategy framework as a foundation for developing a communication strategy capable of instilling trust. According to Kalijodo's video clips and in-depth interviews, the message delivery strategy via Youtube is easily accessible to all residents, and the person conveying the message (the Kalijodo regional head) causes the residents to respond positively to the message conveyed. The communication strategy for educating Kalijodo residents on the value of unity has yielded visible results in the creation of a harmonious life between old and new Kalijodo residents.